A quarter century of Culture's Consequences: a review of empirical research incorporating Hofstede's cultural values framework - Kirkman, Bradley L; Lowe, Kevin B; Gibson, Cristina B (Journal of International Business Studies, 2006)
Since Geert Hofstede's Culture's Consequences: International Differences in Work-Related Values (Sage, 1980) was published, researchers have utilized Hofstede's cultural values framework in a wide variety of empirical studies. We review 180 studies published in 40 business and psychology journals and two international annual volumes between 1980 and June 2002 to consolidate what is empirically verifiable about Hofstede's cultural values framework. We discuss limitations in the Hofstede-inspired research and make recommendations for researchers who use Hofstede's framework in the future.